2018
DOI: 10.3389/fchem.2018.00235
|View full text |Cite
|
Sign up to set email alerts
|

Size and Charge Evaluation of Standard Humic and Fulvic Acids as Crucial Factors to Determine Their Environmental Behavior and Impact

Abstract: In this work, the size and charge of humic and fulvic standards purchased from the International Humic Substances Society are presented and discussed. The secondary structure of humic substances in water environment as well as the size and shape of the dissolved humic species and their changes are ill-defined, very dynamic and can be strongly affected by environmental conditions as the concentration, pH, and ionic strength. They have a strong propensity to aggregate which control their interactions with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 21 publications
1
42
1
1
Order By: Relevance
“…The radionuclide purity is more than 99.9 % (by gamma-ray spectrometer) without other radionuclide impurities. This result complies with the radiopharmaceutical requirement for radionuclidic purity, i.e., ≥ 99.9 % [22].…”
Section: Radionuclide Purity Test Of Na-131 Isupporting
confidence: 85%
“…The radionuclide purity is more than 99.9 % (by gamma-ray spectrometer) without other radionuclide impurities. This result complies with the radiopharmaceutical requirement for radionuclidic purity, i.e., ≥ 99.9 % [22].…”
Section: Radionuclide Purity Test Of Na-131 Isupporting
confidence: 85%
“…While such compounds are attracted to the exchange sites of the resin, the size of these molecules can be limiting. The hydrodynamic radii of these molecules have been determined to be >1.1 nm, with aggregated molecules having diameters in the micro meter range (Kawahigashi et al, 2011;Klučáková, 2018). Size exclusion phenomena can therefore occur as the microporous gel-type resins, with pore sizes typically < 2-4 nm can restrict compounds such as HA and FA to the exterior regions of the resin (Bhandari et al, 2016;Harland, 1994).…”
Section: Influence Of the Size Of Organic Compounds On Their Removalmentioning
confidence: 99%
“…The results of titration experiments with acidic functional groups showed that the carboxyl group content in FA was approximately three times the phenolic hydroxyl group content. Combined with the spectral data for oxygen-containing functional groups in the range of 1000-1800 cm À1 and the relative content of oxygen, the molecular 3,21,[23][24][25][26][27][29][30][31] with the ndings of past research on HA and FA, the numbers and positions of functional groups were continuously adjusted to approximate the experimental test parameters. The resulting two-dimensional planar molecular structure model of FA is shown in Fig.…”
Section: Establishment Of the Molecular Structure Model And Its Theormentioning
confidence: 99%